The museum of Dr. Moses : tales of mystery and suspense - Oates, Joyce Carol, 1938- (Harcourt, 2007)
A collection of tales features "The Man Who Fought Roland LaStarza," "Suicide Watch," "Bad Habits," and "Valentine, July Heat Wave," in which a man sets out to prepare a gruesome surprise for the wife who is planning to leave him.